The stories African lawyers could tell when analysing legal issues: Lessons for social sciences teachers - Zongwe, Dunia P. (HTS teologiese studies, 2021)
Activists and academics have clamoured for the decolonisation of knowledge, including law. But, unfortunately hardly anyone has put forth strategies for how faculties should decolonise the law. A number of jurists have underscored the necessity to draw on customary laws and traditional values. Still, the #RhodesMustFall movement has, for the most part, been loud on the outcomes, but quiet on the methodologies. Joining the conversation on the decolonisation of epistemologies, this article contributes to the ongoing efforts to sanitise the law by proposing to revive African oral storytelling cultures as a way to analyse the questions of law facing society. To live up to this task, this article adopts decolonial theory and, through stylised examples, illustrates how lawyers and social scientists in Africa can utilise storytelling to contextualise, (de)construct, and comprehend those questions. This article assumes that lawyers can use African storytelling alongside the prevailing doctrinal method. That method, relaying the coloniality of law and captured by the acronym IRAC (issue(s), rules, application, and conclusion), trains students to approach conflict in society through a highly abstract and decontextualised problem-solving model. Lately, some (Western) social scientists have (re)discovered the practicality of storytelling in presenting analysis and research. However, in African oral traditions, stories worked differently from the manner in which those scientists employ them. African storytelling played a leading role, not only in conveying collective wisdom and social memory from one generation to the next, but also as a medium through which communities transmit the values that hold them together.Contribution: This article adds to the scholarship on storytelling and narratology by showing how educators can utilise stories to analyse legal questions. That rich scholarship in the humanities and the social sciences has so far not taken seriously the possibility of using stories to analyse research problems. Instead, scholars focus on storytelling mainly as a way of presenting science, not as an analytical tool. This article bridges that gap and demonstrates the analytical value of storytelling.